Analysis of the Strengthening of Bond through Playing Mobile Legends Game with the ”Son of Hippocrates E-SPORT Team” Approach Among Pharmacy Lecturers in the Environment of Kadiri University - Prasetyawan, Fendy; Wahab, Charliandri Saputra; Dhafin, Anis Akhwan; Raharjo, Susilo Margining; Yuniarto, Prayoga Feri (International Journal of Contemporary Sciences (IJCS), 2023)
The surge in Mobile Legends' popularity among pharmacy professors prompts research on its impact on social dynamics and relationships. The game's team strategy elements provide a virtual space for professors to connect, shifting from traditional academic interactions. The research findings illuminate the positive influence of the Son of Hippocrates E-SPORT Team approach in playing Mobile Legends on the interpersonal closeness of pharmacy professors at Kadiri University. Collaborative aspects within the game, such as the creation of strong team bonds, enhanced communication, and support for cooperation beyond the academic sphere, contribute to an improved level of interpersonal relationships among faculty members. The Spearman Correlation Test results (r = 0.245, p = 0.005) support the established positive relationship between Mobile Legends gameplay and the Son of Hippocrates E-SPORT approach among pharmacy lecturers, with the calculated r-value (0.245) surpassing the critical r-value (0.114) and the significance value (0.005) falling below α = 0.05. This acceptance of H1 suggests a meaningful connection between Mobile Legends activities and the Son of Hippocrates E-SPORT